EMPOWERMENT OF BENEFICIARIES OF THE INDONESIAN ECONOMIC HEROES PROGRAM IN DEVELOPING BUSINESSES IN BANDUNG REGENCY - Sundayani, Yana (Indonesian Journal of Social Work, 2026)
Empowerment is the process of empowering and empowering communities to control their lives independently. This study aims to empirically describe the empowerment of beneficiaries of the Indonesian Economic Heroes Program (PENA) in developing micro, small, and medium enterprises in Pasirjambu District, Bandung Regency. The research approach used a quantitative method with a questionnaire survey, resulting in reliability using Cronbach's alpha (α = 0.962). Empowerment is in the high category, with the social aspect at 87.18% and the economic aspect at 94.87%. Based on cross-tabulation, there is a correlation between empowerment and entrepreneurship at 92.30%, indicating that beneficiaries of the PENA program can develop businesses. However, there are still indicators with relatively low results, such as the ability to purchase large commodities and production capabilities. These findings emphasize the need for mentoring to strengthen motivation, improve skills, and provide technical support for production so that the economic empowerment of beneficiaries is more optimal and sustainable. It is also necessary to develop business networks through digitalization and further enhance the ability to develop businesses so that they become more independent.